2007
DOI: 10.2500/aap.2007.28.3054
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of add-on therapy to inhaled fluticasone propionate in children with asthma: Residual volume and exhaled nitric oxide as outcome measures

Abstract: The purpose of this study was to evaluate changes in lung function and fractional exhaled nitric oxide (FeNO) in children with mild to moderate persistent asthma treated with low-dose inhaled steroids but still manifesting significantly increased residual volume (RV). This was a crossover study evaluating lung function and FeNO before and after a 2-week crossover therapy period by adding either montelukast or salmeterol to inhaled fluticasone propionate in 12 children with asthma. Salmeterol increased forced e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The production of FeNO by the inducible NO synthase in the lower airways is upregulated in the presence of a type 2 T‐helper cell inflammation and correlates with the sputum eosinophilic count . Previously, it has been shown that FeNO measurement could be helpful in monitoring of anti‐inflammatory treatment, where it appears to act as a response marker to adjusted anti‐inflammatory therapy . Moreover, an increased FeNO level could indicate an uncontrolled eosinophilic inflammation and could be associated with a heightened future exacerbation risk .…”
Section: Introductionmentioning
confidence: 99%
“…The production of FeNO by the inducible NO synthase in the lower airways is upregulated in the presence of a type 2 T‐helper cell inflammation and correlates with the sputum eosinophilic count . Previously, it has been shown that FeNO measurement could be helpful in monitoring of anti‐inflammatory treatment, where it appears to act as a response marker to adjusted anti‐inflammatory therapy . Moreover, an increased FeNO level could indicate an uncontrolled eosinophilic inflammation and could be associated with a heightened future exacerbation risk .…”
Section: Introductionmentioning
confidence: 99%
“…20,28 FE NO is the most extensively studied exhaled marker in asthma. 6,7,9,29 We showed that mean FE NO significantly decreased after corticosteroid treatment (Fig. 1).…”
Section: Discussionmentioning
confidence: 85%
“…29 The analysis of EBC thus offers new perspectives without any risk for the patient. 31,32 In allergic asthma the steering mechanism is assumed to be bronchial inflammation due to mediators released from eosinophil granulocytes and to the polarization of the immune system toward a reaction state dominated by TH 2 -lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Verini et al [35] revealed that add-on therapy of montelukast reduced the residual volume and decreased the level of FENO, leading to the consideration of a possible anti-inflammatory additive effect that could improve the control of the disease. This disagreement may be due to the personal variability in the treatment response and the significant variability in the course of the disease [36].…”
Section: Discussionmentioning
confidence: 99%